Factors associated with kinesiophobia among myocardial infarction survivors: a biopsychosocial perspective - Zhang, Xiaodan; Li, Yamin; Ma, Qiuping; Jiang, Zheyi; Han, Xinrui; Yi, Keming; Cao, Lifang (Frontiers in psychiatry, 2025)
ObjectivesThis study aimed to examine the factors associated with kinesiophobia among myocardial infarction (MI) survivors.MethodsThis study was based on the Biopsychosocial (BPS) model. A multicenter, descriptive, cross-sectional study was conducted at three tertiary hospitals in Changsha, Hunan Province, China, with MI survivors as participants. The Tampa Scale for Kinesiophobia Heart (TSK-SV Heart), Exercise Self-Efficacy Scale (ESES), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), Self-Perceived Burden Scale (SPBS), the 10-Item Connor-Davidson Resilience Scale (CD-RISC-10), Family Resilience Assessment Scale (FRAS), Multidimensional Scale of Perceived Social Support (MSPSS) and Social Support Rating Scale (SSRS) were used to collect data. Hierarchical regression analysis was employed to identify significant predictors of kinesiophobia.ResultsA total of 414 MI survivors participated. Hierarchical regression analysis showed that the total explanatory power of the model was 56.9%, with sociodemographic factors accounting for 17.0% and cognitive, behavioral, psychological and social support factors accounting for 39.9%. Kinesiophobia was significantly associated with age, gender, education level, disease duration, number of complications, exercise intensity, exercise duration, exercise frequency, exercise self-efficacy (ESE), depression, self-perceived burden (SPB), mental resilience, family resilience, perceived social support (PSS), and actual social support (ASS).ConclusionsThis study identified several sociodemographic, psychosocial, and behavioral factors associated with kinesiophobia in MI survivors. Based on these findings, integrating psychological support, behavior-focused interventions, and strengthened social support systems may help reduce kinesiophobia in this population.